EFFECT OF AFLATOXIN ON TOTAL SERUM PROTEIN AND LIVER GLYCOGEN OF LABEO CALBASU - AMJAD FATMI; D. S. RUBY (The Bioscan, 2011)
In the present investigation the effect of aflatoxin contaminated feed on liver glycogen, total serum protein, serum albumin and serum globulin has been studied on Labeo calbasu collected from river Chambal. A marked decrease in liver glycogen, total serum protein and a simultaneous increase in albumin globulin ratio were noted.